Acting “out-of-the-box” in Montessori teachers’ narratives – research report - Jarosław Jendza (Problemy Wczesnej Edukacji)
In this article the author analyses the situations in which Montessori practitioners experience acting “outside-the-box”. This includes specific “events” in everyday professional practices that are unique, unexpected, somehow special, and therefore do not have any previously prescribed solutions or scenarios. Based on semi-structured, qualitative individual interviews analysis the author outlines the occurrences (usually child initiated) that invite Montessori teachers to “leave” well--known routines, explicitly described procedures and perhaps even the zone of comfort. One of the main results of the research is quite paradoxical. A teacher wanting to act “out-of-the-box”, needs to be consistent with one of the most important Montessori principles, which is following the child. In this sense, Montessori pedagogy can be seen as an open and educational system, inviting various interpretations, and promoting creativity, critical engagement, and innovation, rather than strict rules, clear and reliable methods, or precise techniques mastered during various teacher training courses.